Organizational Commitment and Employee Performance: Examining the Mediating Role of Work Motivation in Healthcare Organizations - Fika Rahmanita; Fiqoh Afriliani; Dadang Dadang (DFAME Digital Financial Accounting Management Economics Journal, 2026)
The study was conducted to understand how psychological and organizational factors contribute to employee work outcomes in a service environment that demands high discipline, responsibility, and productivity. A quantitative associative survey method was applied by distributing questionnaires to hospital employees who met the specified criteria. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to test the relationships among the variables. The study focuses on three main constructs: motivation, organizational commitment, and employee performance. Organizational commitment consists of affective, normative, and continuance dimensions, while motivation includes intrinsic and extrinsic drivers such as recognition, incentives, leadership support, and career opportunities. Employee performance is assessed through quality, quantity, timeliness, and effectiveness. The findings are expected to provide both theoretical and practical contributions to human resource management, particularly in improving employee performance through stronger organizational commitment and higher work motivation.